Students’ perceptions about game-based learning in vocabulary learning - Ismail, Mohammad Rizky Fauzan; Ruswandi, Riki; Hidayat, Hamdan (Univeritas Papua, 2025)
Vocabulary acquisition is a fundamental aspect of language learning. Using suitable learning strategies can help students learn and enrich their vocabulary. This study examines students' perceptions of using Game-Based Learning (GBL) in vocabulary learning. This study was conducted at SMA Istiqamah Bandung, involving 56 grade X students as participants. This study used a quantitative approach with an instrument in the form of a questionnaire distributed via Google Forms. The analysis involved calculating frequency distribution, percentage, mean, and perception levels. We carried out direct communication and periodic reminders to ensure complete data collection. The results indicated that students viewed GBL as a fun and helpful method in learning vocabulary. They showed interest, motivation, and enthusiasm when learning vocabulary through game-based strategies. The findings also reflect a preference for a collaborative, student-centered learning environment. The students viewed GBL as a helpful strategy for vocabulary learning. We recommend further research to explore broader contexts and combine various data collection methods to gain a deeper understanding.